An effectiveness study of Bariederm cream in combined therapy of dermatoses - Z. A. Kuzina; L. A. Anisimova; O. A. Sidorenko; S. V. Grebennikova; V. A. Grebennikov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. The aim of the study is evaluation of the effectiveness of a barrier cream Bariederm in combined therapy of dermatoses. Materials and Methods. 3 groups of patients were examined: 32 patients with allergic contact dermatitis, 22 female patients with cold and wind induced dermatitis and 23 children aged 5 years and under with cutaneons mastocytosis. All of them were treated with Bariederm cream. Results. Including of Bariederm cream in combined treatment fetched to increase of clinical efficiency in treatment of dermatoses. Bariederm cream is also well tolerated.